Daughter of Eden : Eve's story - Smith, Jill Eileen, 1958- (Smith, Jill Eileen, 1958- Daughters of the promised land., 2023)
"Eve has spent all of her days in the Garden, exploring with Adam and walking with their Creator-until the day everything changes. Suddenly she faces darkness she has never before experienced. How will she find the courage to face the unknown future and trust in the promises God has given?"--